The common liver fluke : Fasciola hepatica L. - Pantelouris, E. M. (International series of monographs on pure and applied biology. Division, Zoology, 1965)
The Common Liver Fluke: Fasciola hepatica L. emphasizes the biological, physiological, pathological, and ecology and control of the common liver fluke. The book provides a thorough review of the life of the animal, from its bodily structure to where it thrives. Since this animal can also cause disease, both in livestock and humans, a detailed discussion on its control are also provided.